MORAL MESSAGES ANALYSIS ON ANTOINE DE SAINT-EXUPÉRY’S THE LITTLE PRINCE AND ITS POTENTIAL IN SHAPING YOUNG READERS’ CHARACTER - Annuri, Nur Hairunnisa'; Pratama, Nopal Junanda; Khusniyah, Nurul Lailatul (Citra Media Publishing, 2024)
Moral messages in children's literature play a critical role in shaping the ethical foundations and character development of young readers. This article undertakes an in-depth examination of Antoine de Saint-Exupéry's timeless novella “The Little Prince” to assess its potential influence on child readers. Employing a qualitative approach, the study analyzes the novel's text to identify and explore the novel's significant moral messages. The findings of the analysis reveal that “The Little Prince” imparts profound lessons in imagination, empathy, friendship, loyalty, and responsibility, which deeply shape child readers' understanding and appreciation of these virtues. Through the character of the Little Prince and his journey across planets, the novel demonstrates how a childlike sense of wonder and innocence fosters a deeper perception of beauty and meaning in life. Moreover, the novel emphasizes the importance of caring relationships and the responsibilities that come with them. By providing young readers with these valuable lessons, “The Little Prince” becomes a potent educational tool and a source of moral inspiration for children. Through this analysis, the article underscores the crucial role of children's literature in moral education and the character development of young generations.